Portuguese english: is it possible? analyzing the emergence of an english variety in Portugal - Pernão, Anabela Fé Fonseca (2015)
O objectivo desta dissertação é analisar e alcançar determinadas conclusões acerca do Inglês falado em Portugal e como a Língua Portuguesa pode influenciar este último ou não. Os dados serão recolhidos através de pesquisa teórica e investigação de campo baseados em abordagens quantitativas e qualitativas (questionário e entrevista) aplicados a alunos universitários de várias licenciaturas na Universidade de Évora. O principal objectivo é compreender as atitudes que os estudantes portugueses têm relativamente ao Inglês que utilizam, o nível de proficiência que gostariam de atingir e como vêem estes estudantes uma possível influência da Língua Portuguesa, assim como o aparecimento de uma variante inglesa com características do Português (Portuguese English); ABSTRACT:The purpose of this dissertation is to analyse and draw some conclusions about the English used in Portugal and how the Portuguese language can influence it. Data are collected through theoretical research and fieldwork based on quantitative and qualitative approaches (questionnaire and interview) used with university students from various degree courses at the University of Évora. The main aim of this study is to understand the attitudes Portuguese students have towards the English they use, the English proficiency they would like to acquire and how these students feel about the possible influence of the Portuguese language on the English they use and the emergence of an English variety with Portuguese features (Portuguese English).